Impact of Front Line Demonstrations on the Yield and Economics of Pulse Crops in Burhanpur District of Madhya Pradesh - Singh, Ajeet; Singh, Bhupendra; Jaiswal, Monika; Singh, Kartikey (Indian Journal of Extension Education, 2021)
The study was carried out in adopted villages of Krishi Vigyan Kendra, Burhanpur from 2013-14 to 2018-19. A total of 100 front-line demonstrations were conducted on pulses i.e. black gram, soybean, pigeon pea, chickpea, and green gram in 40 hectares by the active participation of the farmers for adoption of improved technologies of pulse production potentials. The improved technologies included use of new variety and a full package of practices i.e. seed treatment, integrated nutrient management, integrated pest management, irrigation, harvesting, storage and post-harvest management. FLD plot recorded a higher yield compared to farmers' local practice. The mean data revealed that the average yield recorded was 15.74 q/ha under demonstrated plots as compared to farmers' practice 12.50 q/ha. Additional yield over local check was 3.04 q/h with a  percent increased yield of 19.38 per cent. The improved technologies gave higher gross return (Rs 65870/ha), net return (Rs. 46510/ha) with a higher benefit cost ratio (3.09) as compared to the farmer's practice (2.52).